2000
DOI: 10.4049/jimmunol.165.2.725
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Antigen-Specific CD4+ Th2 Cells and B Cells In Vivo Increases Norepinephrine Release in the Spleen and Bone Marrow

Abstract: The neurotransmitter norepinephrine (NE) binds to the β2-adrenergic receptor (β2AR) expressed on various immune cells to influence cell homing, proliferation, and function. Previous reports showed that NE stimulation of the B cell β2AR is necessary for the maintenance of an optimal primary and secondary Th2 cell-dependent Ab response in vivo. In the present study we investigated the mechanism by which activation of Ag-specific CD4+ Th2 cells and B cells in vivo by a soluble protein Ag increases NE release in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 42 publications
0
41
0
4
Order By: Relevance
“…For example, CD86 is stimulated on a B cell during a Th cell-B cell interaction in either the initial Ag presentation event to a resting Th2 cell (13) or during interaction with a previously activated Th2 cell (58). On the other hand, the ␤ 2 AR on a B cell is stimulated by norepinephrine released from nerve terminals residing within the parenchyma of lymphoid tissue in the B cell microenvironment shortly after Ag entry (28). Thus, the stimulation of both CD86 and ␤ 2 AR on a B cell may help to regulate the level of normal B cell activity in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, CD86 is stimulated on a B cell during a Th cell-B cell interaction in either the initial Ag presentation event to a resting Th2 cell (13) or during interaction with a previously activated Th2 cell (58). On the other hand, the ␤ 2 AR on a B cell is stimulated by norepinephrine released from nerve terminals residing within the parenchyma of lymphoid tissue in the B cell microenvironment shortly after Ag entry (28). Thus, the stimulation of both CD86 and ␤ 2 AR on a B cell may help to regulate the level of normal B cell activity in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, stimulation of the ␤ 2 AR on a B cell, which serves as the receptor for the neurotransmitter norepinephrine that is released in the B cell microenvironment within lymphoid organs (28), increases the level of CD86 expressed on and IgG1 produced by a B cell activated in vitro in the presence of a Th2 cell or CD40L/IL-4 (16). Since the Th2 cell did not express ␤ 2 AR, it was concluded that stimulation of ␤ 2 AR on a B cell most likely had a direct effect on IgG1 production.…”
Section: Selective Regulation Of Mature Igg1 Transcription By Cd86mentioning
confidence: 99%
See 1 more Smart Citation
“…These findings also suggest that following both BCR and ␤ 2 AR stimulation, a higher level of CD86 would be available on the B cell surface at the initiation of an Ab response, perhaps to ensure optimal B cell activation during an Ag-specific response in vivo. Such an event is likely given that the amount and turnover of norepinephrine in the spleen increases after Ag administration (16,60).…”
Section: Discussionmentioning
confidence: 99%
“…All immune organs receive innervation from tyrosine hydroxylase-positive fibers, suggesting that the release of neurotransmitters, such as norepinephrine (NE), by the sympathetic nervous system (SNS) could impact the function of immune cells (3,4). Indeed, an increase in NE release in the spleen was described following the activation of Ag-specific Th cells and B cells, indicating that SNS activation occurs during an ongoing adaptive immune response and, thus, may influence its course (5). Particularly in the spleen and lymph nodes, the sympathetic innervation is restricted to the T cell zones where dendritic cells (DC) are also present (3,4).…”
mentioning
confidence: 99%